Ultrafast Osmotic Distillation for Cranberry Juice Concentration with Hydrophilic Ionic Liquid as Receiving Phase - Zuniga-Navarro, G; Romero-Figueroa, J; Quijada-Maldonado, E; Olea-Chandia, F; Zurob-Guzman, E (Elsevier Ltd, 2025)
This study presents an innovative application of the hydrophilic ionic liquid (IL) 1-methyl-3-octylimidazolium chloride as a novel receiving phase in the osmotic distillation (OD) process for cranberry juice concentration. A hydrophobic hollow fiber membrane module was employed, operating at a 10:1 juice-to-IL volumetric ratio and 30 °C, achieving a maximum transmembrane flux of 2.5 kg m−2 h−1. The findings demonstrate the potential of ILs to enhance process efficiency while preserving key quality attributes like total soluble solids, phenolic compounds, and aroma which are critical for consumer acceptance. A resistance-in-series mathematical model accurately predicted mass and heat transfer behavior, identifying the membrane pores as the dominant resistance to mass transfer, approximately 400 times greater than other transport steps. Compared to conventional OD using saturated CaCl₂ brine and flash drying techniques, IL-based OD showed superior performance in retaining sensory and nutritional quality, while also reducing energy consumption. This study contributes to the development of scalable and resource-efficient food processing technologies by demonstrating the feasibility of ILs as emerging alternatives for gentle concentration processes. The results offer meaningful implications for sustainable food production, aligning with current industry demands for mild, innovative processing strategies that preserve high-value product integrity and extend shelf life. © 2025 Elsevier Ltd
Keywords: Osmotic distillation; Ionic liquids; Cranberry juice concentration; Sustainable food processing; Emerging separation technologies; Food quality preservation